The influences of abusive supervision on job satisfaction and mental health: the path through emotional labor. Issue 2 (26th February 2021) - Wang, I-An; Lin, Szu-Yin; Chen, Yeong-Shyang; Wu, Shou-Tsung
Abstract : Purpose: The purpose of the study is to empirically test and explore the influences of abusive supervision on subordinates' job satisfaction and mental health. Specifically, the authors focus on the mediation effects of emotional labor and compare the discrepancies between surface acting and deep acting. Design/methodology/approach: Time-lagged data were obtained from 239 employees in the hospitality industry in Taiwan. The hypothesized model was tested using structural equation modeling with Mplus 7.4. Findings: Results showed that abusive supervision is not only negatively related to employees' job satisfaction and mental health but also positively associated with employee surface acting and negatively associated with deep acting. For mediating effects, surface acting mediates the relationships between abusive supervision and employee job satisfaction, while deep acting mediates the relationship between abusive supervision and mental health. Practical implications: Abusive supervision is detrimental; it should be reduced in the workplace. Also, frontline employees can be provided with training programs to improve their deep acting strategies, which lead to better job satisfaction and mental health. Originality/value: This research is among the first to examine the link between abusive supervision and both employee job satisfaction and mental health in the hospitality industry and extends the authors' knowledge by demonstrating the mediating effects of surface acting and deep acting.